2020
DOI: 10.1039/c9sc05248h
|View full text |Cite
|
Sign up to set email alerts
|

α-Glucuronosyl and α-glucosyl diacylglycerides, natural killer T cell-activating lipids from bacteria and fungi

Abstract: Microbial α-glycosyl diacylglycerides when presented by the antigen presenting molecule CD1d are recognized by both classical type I and atypical Natural Killer T cell receptors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Other diacylglycerols (DAGs) are found in the cell walls of Corynebacterium glutamicum , an uniquitous soil bacterium without clinical relevance, Mycobacterium tuberculosis , Listeria monocytogenes and Mycobacterium smegmatis , a fast-growing, non-pathogenic bacterial species usually detected in urogenital secretions. Interestingly, α-glucuronosyl diacylglycerol (α-GlcA-DAG) derived from Mycobacterium smegmatis stimulated a NKT cell subset carrying a semi-invariant α-chain Vα10-Jα50 + ( Uldrich et al., 2011 ; Burugupalli et al., 2020 ) as well as type 2 NKT cells ( Almeida et al., 2019 ). Although Vα10-Jα50 + NKT cells recognized α-GalCer presented by CD1d, they neither fit in the type 1 nor the type 2 NKT cell category.…”
Section: Nkt Cell Antigensmentioning
confidence: 99%
See 2 more Smart Citations
“…Other diacylglycerols (DAGs) are found in the cell walls of Corynebacterium glutamicum , an uniquitous soil bacterium without clinical relevance, Mycobacterium tuberculosis , Listeria monocytogenes and Mycobacterium smegmatis , a fast-growing, non-pathogenic bacterial species usually detected in urogenital secretions. Interestingly, α-glucuronosyl diacylglycerol (α-GlcA-DAG) derived from Mycobacterium smegmatis stimulated a NKT cell subset carrying a semi-invariant α-chain Vα10-Jα50 + ( Uldrich et al., 2011 ; Burugupalli et al., 2020 ) as well as type 2 NKT cells ( Almeida et al., 2019 ). Although Vα10-Jα50 + NKT cells recognized α-GalCer presented by CD1d, they neither fit in the type 1 nor the type 2 NKT cell category.…”
Section: Nkt Cell Antigensmentioning
confidence: 99%
“…Compared to other antigens, the abundance of NKT cell ligands in the cell wall of both bacteria might be lower. Moreover, the stimulatory capacity of PIM4 and cholesteryl α-glucosides has not been compared yet with the exception of a study testing few NKT cell clones ( Burugupalli et al., 2020 ) to the one of GSLs or DAGs found in other bacteria. Nonetheless, we speculate that the NKT cell TCR might have evolved as a pattern recognition receptor for distinct classes of bacteria carrying GSLs or DAGs in their cell walls.…”
Section: Nkt Cell Antigensmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors 13 proved that GlcA-DAG accumulate not only in model plants but also in tomato and soybean ones grown in P-limited conditions, and their concentration is greatly elevated concomitantly with the upregulation of SQDG synthase transcripts. Very recently, Burugupalli et al 21 reported an efficient synthesis of α-GlcA-DAG analogues, demonstrating that they can be recognized by T cell receptors derived from type I and atypical natural killer T cells. Among higher plants, tomato (Solanum lycopersicum L.), belonging to the family of Solanaceae, is one of the most cultivated vegetables in the world and constitutes the basic element of the Mediterranean diet, being the emblem of typical and distinctive dishes, and a source of valuable bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to bacteria, lipid antigens from fungus and protozoan parasites were also reported to induce NKT responses (32), but no virus lipid antigen has been found, although the activation of NKT cells are well documented in viral infections (33,34). Moreover, in the condition of bacterial infections, endogenous lipid antigens such as isoglobotrihexosylceramide NKT cell subsets can be grouped into four categories mainly based on their cytokine patterns and function, similarly like classical CD4 T cell subsets.…”
Section: The Activation Of Nkt Cells and The Role Of Dcsmentioning
confidence: 99%